Health‐related quality of life in survivors of acute kidney injury: The Prolonged Outcomes Study of the Randomized Evaluation of Normal versus Augmented Level Replacement Therapy study outcomes. (July 2015) - Wang, Amanda Y; Bellomo, Rinaldo; Cass, Alan; Finfer, Simon; Gattas, David; Myburgh, John; Chadban, Steve; Hirakawa, Yoichiro; Ninomiya, Toshiharu; Li, Qiang; Lo, Serigne; Barzi, Federica; et al.
Abstract: Aim: While patients with chronic kidney disease have reduced health‐related quality of life (HRQOL), long‐term HRQOL of survivors of severe acute kidney injury (AKI) remains unclear. Methods: We analysed HRQOL from the Prolonged Outcomes Study of the Randomized Evaluation of Normal versus  Augmented Level Replacement Therapy (POST‐RENAL) study and compared findings with those from a general Australian adult population enrolled in the Australian Diabetes, Obesity and Lifestyle (AusDiab) study. We used a multivariate analysis adjusted for baseline characteristics along with sensitivity analysis using age and sex‐matched case controls. Results: In the POST‐RENAL study, 282 participants had HRQOL data collected using the SF‐12 questionnaire. This was compared with 6330 participants from the AusDiab study. Unadjusted analyses showed that POST‐RENAL participants had lower physical component scores (PCS, mean score 40.0 vs 49.8, P  < 0.0001) and lower mental component scores (MCS, mean score 49.8 vs 53.9, P  < 0.0001) than the AusDiab group. After age and sex matching, the difference in PCS and MCS remained statistically significant ( P  < 0.0001). Advanced age, reduced renal function and albuminuria (all P  ≤ 0.01) were all strongly associated with lower PCS values but not MCS values. After matching subsets of the cohorts on the basis of age, sex and renal function, PCS and MCS were lower in the POST‐RENAL group ( P  < 0.0001). Conclusion: Survivors of severe AKI in the POST‐RENAL study had lower physical and mental components of HRQOL compared with general population, even after adjustment for their reduced renal function. Increasing age and reduced renal function were associated with poorer physical QOL. Summary at a Glance: In this case‐control study, the health‐related quality of life (HRQOL) of 282 severe acute kidney injury (AKI) survivors was compared with that of the general population. The result shows that physical and mental components of HRQOL are substantially lower amongst survivors of severe AKI. The difference remains significant after adjustment for the degree of renal impairment.